PENAFSIRAN IDEOLOGIS PERSPEKTIF ASBÂB AL-KHATÂ’ FÎ AL-TAFSÎR - Fiqih Kurniawan (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2020)
It is believed that the Prophet Muhammad's interpretation of the Qur'anic verses was not carried out thoroughly, thus leaving some empty space for the generation of companions to understand and interpret verses that were not explained by the prophet, as well as to the tabiin generation. On the other hand, the Koran was not only interpreted by the pioneers of that generation, but was also politicized by religious traditions. This paper does not intend to describe historical aspects, but rather emphasizes how the Qur'an was twisted for the sake of school and politics. The results of the drafting and interpretations that were carried out were later identified as misinterpretations. There are two interpretations in the spotlight: the post-war Khawarij sect Ṣiffin between 'Ali and Muawiyah and the interpretation of  Zamakhshari in the book al-Kashshâf. By using the perspective of asbâb al-khaṭâ 'fî al-tafsîr, some of their interpretations are categorized as wrong interpretations for several reasons. First, the exaggerated subjectivity of the commentators; second, not paying attention to context; third, partially distorting the verses of the Qur'an to support the corrupted sects; fourth, inclined towards temperament and lust; fifth, too deep in talking about kalam and philosophy.Keywords: Asbâb al-Khaṭâ’ fî al-Tafsîr, Ideological aspect, Periodization of the interpretation                                                                     Penafsiran Nabi Muhammad terhadap ayat Alquran dipercayai tidak dilakukan secara menyeluruh, sehingga meninggalkan sebagian ruang kosong bagi generasi sahabat untuk memahami dan menafsirkan ayat yang tidak dijelaskan oleh nabi, begitu pun sampai kepada generasi tabiin. Di pihak lain, Alquran tidak melulu ditafsirkan oleh pionir generasi tersebut, tetapi pula dipolitisir oleh aliran keagamaan. Tulisan ini tidak bermaksud memaparkan aspek sejarah, melainkan lebih menekankan pada bagaimana Alquran dipelintir untuk kepentingan mazhab dan politik. Hasil pencatutan dan penafsiran yang dilakukan belakangan diidentifikasi sebagai penafsiran yang keliru. Ada dua penafsiran yang menjadi sorotan: sekte Khawarij pasca perang Ṣiffin antara ‘Ali dan Muawiyah dan penafsiran Zamakhshari dalam kitab al-Kashshâf. Dengan menggunakan perspektif asbâb al-khaṭâ’ fî al-tafsîr, sebagian penafsiran mereka dikategorikan sebagai penafsiran yang salah karena beberapa sebab. Pertama, subjektivitas mufasir yang berlebihan; kedua, tidak memperhatikan konteks; ketiga, mencatut ayat Alquran secara parsial untuk mendukung mazhab yang rusak; keempat, condong pada perangai dan hawa nafsu; kelima, terlalu mendalam dalam berbicara ilmu kalam dan filsafat.Kata Kunci: Asbâb al-Khaṭâ’ fî al-Tafsîr, Aspek Ideologi, Pembabakan Tafsir